Structural and thermoelectric properties of the type-I Sn clathrates Cs8Sn46−n(n=0, 2) from Density Functional Theory (DFT). (8th February 2018) - Egbele, Peter O.; Shoko, Elvis; Joubert, Daniel P.
Abstract: Sn clathrates are promising phonon glass, electron crystal materials (PGEC), in which the phonon free paths are short and the electron free paths are long. We analysed the relaxed structure of Sn clathrates using four different Density Funtional Exchange-Correlation functionals. The phonon structures were investigated as a first step in order to determine the phonon contribution to the thermal conductivity. We determined the Seebeck coefficient and electrical conductivity of the clathrate compound and the thermoelectric figure of merit. A glimpse into the dynamics of the system for the evaluation of the thermoelectric and electronic properties is presented.